Opening Remarks on Food Prices - Zoellick, Robert B. (World Bank, 2016)
Robert B. Zoellick noted that the World Bank release of the Food Price Watch underscores the need for the G20 to put food first. The key driver behind the upward spiral in the food price index has been sharp rises in the prices of wheat, maize, sugar and oils. Global food price hikes have pushed about 44 million people into extreme poverty. He called for global action to turn things around—help for small holder farmers, with seeds and fertilizer; better weather forecasting; better means to get produce to markets; food and effective safety nets for the most vulnerable people. We need to do a better job of feeding the hungry today before we face the future challenges of feeding the expected nine billion people in the world in 2050.